Incorporation of nanoparticles in metal-organic frameworks materials for catalysis - Siow, Kai Yuan. (2013)
Metal organic framework incorporated with various nanoparticles composites were investigated for the oxidation of benzyl alcohol to benzyl aldehyde. Promising catalysis conversion and selectivity were obtained in this project, 45% and 100% respectively. Those high catalysis conversion and selectivity were obtained by having good synthesis methods for the nanoparticles and thereafter, good encapsulation method to incorporate the nanoparticles into the metal organic framework. Metal organic framework used in this project was zeolitic imidazolate framework 8, it provided selectivity via the small pore aperture of 3.4Å and allow nanoparticles to reside on its high pore surface area of over 1,500m2/g. As for nanoparticles, cerium oxide and palladium were used. Both nanoparticles were synthesized into desired shape and size, nanocube with about 5nm edge length for cerium oxide and nanosphere with about 3nm diameter for palladium. Surfactant grafting of polyvinylpyrroidone for the nanoparticles was successful and proven to be an essential step to ensure good encapsulation. Apart from surfactant grafting, prolong sonication of 8hours and the use of right concentration of nanoparticles for encapsulation were shown to be equally important for good encapsulation. Overall, with the comprehensive approach towards the making of the metal organic framework incorporated with various nanoparticles composites, this project has comparable and promising catalysis conversion and selectivity.